To eliminate x, multiply eq.1 by 2 to make the coefficeints of x equal

-2x+4y=10 -----> 3

-2x+3y=9 ------> 2

Subtract 3 from 2,

y = 1

So Substituting the yalue of 'y' in eq.1 we get,

-x + (2*1) = 5

-x + 2 = 5

-x = 3

So x = -3

y = 1

Please let me know if you need any clarification. I'm always happy to answer your questions.

Jul 24th, 2015

I am sorry... the above method was elimination method.

Please find below the answer by substitution method..........................................................................................................

Jul 24th, 2015

-x+2y=5 -----> 1

-2x+3y=9 ------> 2

From eq.1 x = 2y-5

-2 (2y-5) +3y = 9

-4y+10+3y = 9

-y+10 = 9

-y = -1

y =1

So Substituting the yalue of 'y' in eq.1 we get,

-x + (2*1) = 5

-x + 2 = 5

-x = 3

So x = -3

y = 1

Jul 24th, 2015

Hi Can u pls go to the home page and add my name under promotion you will get 10$ free.